IMPLEMENTASI LINGUISTIK TENTANG GENDER DALAM ALQURâ€™Ã‚N TERHADAP HUKUM ISLAM - Saladin, Bustami (OKARA: Jurnal Bahasa dan Sastra, 2011)
Arabic has an important position in Islamic studies, in the development of Arabic, the language al-Qur’Ã¢n can be classified into classical Arabic, the language al-Qur’Ã¢n which developed into a literary language since the 7th century AD. Thanks to the altitude of the language al-Qur’Ã¢n precisely then that the experts make the standardization of the Arabic language is academic in the 3rd century H (9 M) and 4 H (10 M). In the process of standardization is determined systematics grammatikal, syntax, vocabulary, and the use of literature through a variety of in-depth research activities Arabic has an important position in Islamic studies, in the development of Arabic, the language al-Qur’Ã¢n can be classified into classical Arabic, the language al- Qur’Ã¢n which developed into a literary language since the 7th century AD. Thanks to the altitude of the language al-Qur’Ã¢n precisely then that the experts make the standardization of the Arabic language is academic in the 3rd century H (9 M) and 4 H (10 M). In the process of standardization is determined systematics grammatikal, syntax, vocabulary, and the use of literature through a variety of in-depth research activities